Influence of abiotic factors on seasonal abundance of natural enemies on safflower during rabi season: Influence of abiotic factors on seasonal abundance of natural enemies on safflower during rabi season - S C KUMBHAR,; D S MUTKULE,; M V DHUPPE, (Journal of Oilseeds Research, 2020)
An experiment was conducted to observe the influence of abiotic factors on seasonal abundance of naturalenemies on safflower at oilseed research station, Latur, Maharashtra during rabi 2016-17. The incidence of lady bird beetle was recorded from 45th standard meteorological week (SMW) to 08th SMW. The incidence started at 21 days after germination of safflower crop i.e. 0.1 ladybird beetle/5 cm twig/plant during 48th standard meteorological week and reached to its peak (0.7 beetle/plant) during 2nd Standard meteorological week and recorded peak of 0.7 ladybird beetle/5 cm twig/plant and there after population decreased. The weather parameters viz., low temperature, high humidity showed significant role in multiplication ladybird beetle. The weather parameters during the peak incidence of ladybird beetle were maximum temperature-26.50C, minimum temperature-11.6°C, morning relative humidity of 82% and evening relative humidity of 38%.